Identification of volatile compounds in several meat and bone broth using Solid Phase Micro Extraction-Gas Chromatography Mass Spectrometry (SPME-GCMS) for initial detection of Halal and Non-Halal Food - Diana Candra Dewi; Chanif Mahdi; Hermin Sulistyarti; Aulani`am Aulani`am (Chemistry Department, The University of Brawijaya, 2023)
The development of techniques for detecting halal and non-halal animal meat is of great importance as a useful tool for monitoring and assuring food quality for Muslim. Flavor or aroma is one of the sensory attributes for consumers to distinguish broth cattle. The differences aroma of broth cattle is contributed by the content of volatile compounds. This study was aimed to determine the composition of volatile compounds in meat and bone broth from five different animals, i.e., cow (beef), pig (pork), goat, lamb, and chicken for initial identification of halal and non halal food. A preliminary test for samples of meat and bone broth was done by identifying their physical properties including pH, viscosity, and density. The volatile compounds in meat and broth samples were extracted using a solid phase-micro extraction (SPME) at room temperature and analyzed by gas chromatography-mass spectrometry (GCMS). The results revealed the physical properties of meat and bone broth, i.e. pH, viscosity, and density, cannot be used to distinguish the type of broth produced from beef, pork, goat, lamb, and chicken. Successful results for the identification were achieved through chromatogram profile of volatile compounds from meat and bone broth which show characteristics to each type of animal, and therefore it can be used to distinguish pork from beef, goat, lamb, and chicken as initial detection for halal and non halal food. The research also identified 7 predominant volatile compounds as a marker for meat pork and other 8 specific compounds marker for pork bone.